2010
DOI: 10.1590/s1806-83242010000400015
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of low intensity laser on the cytotoxicity produced by substances released by bleaching gel

Abstract: This in vitro study aimed to analyze the effect of different parameters of phototherapy with low intensity laser on the viability of human dental pulp fibroblasts under the effect of substances released by bleaching gel. Cells were seeded into 96 wells plates (1 x 10 3 cells/well) and placed in contact with culture medium conditioned by a 35% hydrogen peroxide bleaching gel for 40 minutes, simulating the clinical condition of the in-office bleaching treatment. Cells cultured in ideal growth conditions served a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 28 publications
3
58
1
2
Order By: Relevance
“…However, the laser protocols tested were not capable of influencing the metabolism of previously damaged odontoblast-like cells. These data were not corroborated by results from in vitro studies in which osteoblasts, odontoblasts, or even fibroblasts exposed to bleaching agents were positively modulated by low-level laser irradiation [26,29,30]. The differences observed when results of these investigations were compared with those from the present study may be at least partly due to the variable parameters of the laser protocols tested (wavelength, potency, energy density).…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…However, the laser protocols tested were not capable of influencing the metabolism of previously damaged odontoblast-like cells. These data were not corroborated by results from in vitro studies in which osteoblasts, odontoblasts, or even fibroblasts exposed to bleaching agents were positively modulated by low-level laser irradiation [26,29,30]. The differences observed when results of these investigations were compared with those from the present study may be at least partly due to the variable parameters of the laser protocols tested (wavelength, potency, energy density).…”
Section: Discussioncontrasting
confidence: 96%
“…Analysis of the data obtained in the present study, and other previous investigation [26] , indicated that low-level laser irradiation may represent an alternative therapy for the modulation of pulp cell responses against the toxic effects caused by bleaching agent components capable of diffusing across dental hard tissues, i.e., enamel and dentin. Nevertheless, other factors, such as the number of laser irradiations and the energy doses used, need to be evaluated in further studies.…”
Section: +supporting
confidence: 65%
See 1 more Smart Citation
“…In this study, the conditioned medium remained in contact with the cells for just 30 min, because pilot studies have shown that after this period, the bleaching agents becomes extremely toxic, making it impossible to realize this type of research. This data is according with the study of Dantas et al [26], that placed the conditioned medium is contact with the cells for 40 min. Moreover, Soares et al [27], evaluated the cytotoxicity of 35% Hydrogen peroxide and different periods of contact of the gel with odontoblast-like cells (MDPC-23) and conclude that cytotoxic effects were proportional to the contact time of the bleaching gel.…”
Section: Discussionmentioning
confidence: 65%
“…The AAPD does not indicate the total arch treatment for patients with mixed dentition. 15 Taking into account that a young patient's pulp is wider than that of an adult patient, and that the diffusion of hydrogen peroxide at high concentrations into dental tissues is extensive, [16][17][18] a safer treatment was selected for the current patient: 10% carbamide peroxide, reducing the possibility of sensitivity. [19][20][21] This treatment was performed in an individualized way for this patient: using direct applications on the more pigmented areas followed by application with personal trays for 14 days, and only with the affected teeth.…”
Section: Discussionmentioning
confidence: 99%